2022
DOI: 10.3389/fphar.2022.888333
|View full text |Cite
|
Sign up to set email alerts
|

Association between antibiotics and dementia risk: A retrospective cohort study

Abstract: Background: The possible relation between antibiotic exposure and the alteration of gut microbiota, which may affect dementia risk, has been revealed. However, the association between antibiotics and dementia incidence has rarely been studied. We aimed to determine the association between antibiotic exposure and the risk of dementia.Methods: This population-based retrospective cohort study used data from the National Health Insurance Service-Health Screening Cohort (NHIS-HEALS) in South Korea. Exposure was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…Furthermore, prolonged administration of some antimicrobial medications, such as vancomycin, ampicillin, and streptozocin, may induce profound changes in the gut microbiota composition, altering the gut–brain axis involved in the pathogenesis of several neurodegenerative disorders [ 162 165 ]. A cumulative duration-dependent relationship between dementia incidence and days of antibiotic exposure recently emerged in a retrospective cohort study [ 166 ]. The association was significant after adjustment for several confounding factors potentially related to cognitive decline, including infectious diseases and dysphagia [ 166 ].…”
Section: Clinical Profile Of Older Patients At Risk Of Adverse Events...mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, prolonged administration of some antimicrobial medications, such as vancomycin, ampicillin, and streptozocin, may induce profound changes in the gut microbiota composition, altering the gut–brain axis involved in the pathogenesis of several neurodegenerative disorders [ 162 165 ]. A cumulative duration-dependent relationship between dementia incidence and days of antibiotic exposure recently emerged in a retrospective cohort study [ 166 ]. The association was significant after adjustment for several confounding factors potentially related to cognitive decline, including infectious diseases and dysphagia [ 166 ].…”
Section: Clinical Profile Of Older Patients At Risk Of Adverse Events...mentioning
confidence: 99%
“…A cumulative duration-dependent relationship between dementia incidence and days of antibiotic exposure recently emerged in a retrospective cohort study [ 166 ]. The association was significant after adjustment for several confounding factors potentially related to cognitive decline, including infectious diseases and dysphagia [ 166 ]. Furthermore, exposure to long-term antibiotic use during mid-life was recently associated with decline in cognitive performance [ 167 ].…”
Section: Clinical Profile Of Older Patients At Risk Of Adverse Events...mentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of an association between antibiotic usage and various types of cancer, including prostate cancer, has been suggested in previous studies [6][7][8]. Previous cohort studies have reported that long-term antibiotic exposure may be associated with the risk of other diseases such as diabetes, dementia, and obesity [9][10][11]. The effects of antibiotics on gut microbiota diversity reduction and alteration have been revealed [12].…”
Section: Introductionmentioning
confidence: 99%